2014
DOI: 10.3389/fmicb.2014.00427
|View full text |Cite
|
Sign up to set email alerts
|

The biocontrol endophytic bacterium Pseudomonas fluorescens PICF7 induces systemic defense responses in aerial tissues upon colonization of olive roots

Abstract: Pseudomonas fluorescens PICF7, a native olive root endophyte and effective biocontrol agent (BCA) against Verticillium wilt of olive, is able to trigger a broad range of defense responses in root tissues of this woody plant. In order to elucidate whether strain PICF7 also induces systemic defense responses in above-ground organs, aerial tissues of olive plants grown under non-gnotobiotic conditions were collected at different time points after root bacterization with this endophytic BCA. A suppression subtract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 84 publications
(124 reference statements)
5
75
0
Order By: Relevance
“…Pseudomonadaceae are reported to exhibit a wide range of plant-beneficial properties and plant growth-promoting traits. These include phosphate solubilization, nitrogen fixation, synthesis of cytokinins as well as of the phytohormones indole-3-acetic acid (IAA) and gibberellins (Cabanas et al, 2014; Vacheron et al, 2016). The latter was reported to affect seed formation and ripening in grasses (Stoddart, 1965; Kim et al, 2016), emphasizing the importance of Pseudomonadaceae in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonadaceae are reported to exhibit a wide range of plant-beneficial properties and plant growth-promoting traits. These include phosphate solubilization, nitrogen fixation, synthesis of cytokinins as well as of the phytohormones indole-3-acetic acid (IAA) and gibberellins (Cabanas et al, 2014; Vacheron et al, 2016). The latter was reported to affect seed formation and ripening in grasses (Stoddart, 1965; Kim et al, 2016), emphasizing the importance of Pseudomonadaceae in our study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best BCA of VWO so far studied is the olive root endophyte P. fluorescens PICF7 (Mercado‐Blanco et al ., ; Prieto et al ., 2009; 2011). Strain PICF7 is able to trigger a broad range of defence responses in both root (Schilirò et al ., ) and aerial (Gómez‐Lama Cabanás et al ., ) tissues, pointing to a scenario in which VWO biocontrol by PICF7 could be mediated by induced resistance mechanism(s) (Pieterse et al ., ). We have recently shown, however, that the presence of PICF7 cells in root tissues does not suppress olive knot disease in stems caused by Pseudomonas savastanoi pv.…”
Section: Discussionmentioning
confidence: 99%
“…FP12 (Papasotiriou et al, 2013). The endophytic BCA P. fluorescens PICF7 has been shown to activate an array of defense pathways in the roots and aerial tissues of olive upon colonization of the roots (Schilirò et al, 2012; Gómez-Lama Cabanás et al, 2014). Recently, Gómez-Lama Cabanás et al (2017) demonstrated that the expression of defense-related genes differed depending on whether or not V. dahliae and P. fluorescens PICF7 colonized the same sectors of the roots of olive plants.…”
Section: Biological Control Of Verticillium Wiltmentioning
confidence: 99%